2012
DOI: 10.4049/jimmunol.1201309
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide and Sphingosine-1-Phosphate Cooperate To Induce Inflammatory Molecules and Leukocyte Adhesion in Endothelial Cells

Abstract: Given that TLRs and sphingosine-1-phosphate (S1P) are key players in inflammation, we explored the potential interplay between TLRs and S1P in the adhesion/inflammatory pathways in primary human endothelial cells. As determined by Western blot and flow cytometry, cells treated with LPS (a TLR4 ligand) and S1P showed significantly enhanced expression of adhesion molecules such as ICAM-1 and E-selectin compared with the effect of either ligand alone. Cell-type differences on E-selectin upregulation were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 39 publications
3
61
1
Order By: Relevance
“…43,44 As S1P, S1P1 has been linked to proinflammatory responses and anti-inflammatory responses. 10,11 However, the use of a specific aortic endothelium S1P1 knock-out mouse strongly supports the anti-inflammatory role of S1P1, 13 which is in consonance with our findings in human endothelium. Along the same line, HDL promotes the formation of endothelial adherent functions and endothelial barrier function through ApoM-bound S1P and the S1P1 receptor.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…43,44 As S1P, S1P1 has been linked to proinflammatory responses and anti-inflammatory responses. 10,11 However, the use of a specific aortic endothelium S1P1 knock-out mouse strongly supports the anti-inflammatory role of S1P1, 13 which is in consonance with our findings in human endothelium. Along the same line, HDL promotes the formation of endothelial adherent functions and endothelial barrier function through ApoM-bound S1P and the S1P1 receptor.…”
supporting
confidence: 80%
“…It is possible that the HDL size limits the ApoM and S1P1 interaction. S1P 0.01 µmol/L was not statistically significant for any of the treatments.Given that (1) exogenous stimulation of noncarrier-mediated S1P on endothelial cells is often described as a proinflammatory stimulus, [10][11][12] (2) most albumin molecules in plasma do not carry S1P, (3) S1P is largely bound to ApoM, and (4) ApoM-bound S1P is more potent anti-inflammatory than albumin-S1P, we conclude that ApoM takes up a prominent role in S1P biology and vascular homeostasis. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in their counterpart A7 melanoma cells that express FLNA, S1P does not activate NF-B unless the expression of FLNA is downregulated. Several previous reports suggested that S1P can activate NF-B via S1PRs (14,15,(29)(30)(31)(32)(33)(34). Although in some studies, the S1PR involved was not identified and the concentration of S1P used was too high to substantiate the involvement of S1PR-mediated events (35), others have clearly implicated S1PR1 to -3 in different cell types.…”
Section: Discussionmentioning
confidence: 79%
“…Subsequently, specific antisense oligonucleotides were used to show that the activation of NF-B in HUVECs requires mainly S1PR3 and, to a much lesser extent, S1PR1 (15). Moreover, pharmacological and siRNA experiments substantiated the involvement of S1PR1 and S1PR3 in NF-B activation in cooperation with lipopolysaccharide (LPS) to induce inflammatory molecules and leukocyte adhesion in endothelial cells (29). Surprisingly, S1PRs have been linked not only to stimulatory pathways leading to the activation of NF-B but also to inhibitory pathways in HUVECs.…”
Section: Discussionmentioning
confidence: 99%